Problem Based Learning Model Based On Image Media In Mastering Mufradat And Kalam For Arabic Language And Literature Students/ نموذج التعلم المبني على المشكلة القائم على الوسائط الصورية في إتقان مفردات ومهارة الكلام لطلبة القسم اللغة العربية وآدابها - Mawardy, Naja Alwi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to explain the problem-based learning model in the Department of Arabic Language and Literature, Sayyid Ali Rahmatullah State Islamic University, Tulungagung, Indonesia. The research method used is a qualitative approach, especially phenomenology. Data collection techniques include observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and conclusion. Apart from that, literature data analysis uses descriptive analysis and content analysis. This research will focus on discussions related to the role of lecturers as planners, implementers, and evaluators in the application of problem-based learning models based on image media in mastering vocabulary and speaking skills. The research results show that the problem-based learning model used in